Identifiying factors influencing plagiarism among undergraduate students using fuzzy analytic hierarchy process (F-AHP) / Anis Nadia Anuar - Anuar, Anis Nadia (2021)
Plagiarism has become a common phenomenon among students, especially in higher education. This is because students are not aware of the meaning on plagiarism. If this problem is not corrected, there will be many cases of students copying other people's work, and this habit will be carried on to their workplace. To overcome this issue, it might be helpful to find out the causes of the problem. The objective of the research is to investigate the main factor that influence plagiarism among undergraduates based on easy access to the internet, gender, pressure in study, students' academic skills, awareness of plagiarism and teaching factors. Therefore, this study proposes a solution by developing a mathematical technique which is Fuzzy Analytical Hierarchy Process (F-AHP) to determine the main factor that influence plagiarism among undergraduates. Based on the results of the research, easy access to the internet has shown to be the strongest factor that influence plagiarism among undergraduate students in UiTM Perlis which has the highest normalized value. In conclusion, it can be said that this study has added proof to the existing research that the internet has made it easy for the students to plagiarize. However, future works and improvements can be initiated by related organizations particularly the Department of English Language (APB) to reduce the number of plagiarisms among students in UiTM Perlis.